KOMUNIKASI CSR PERUSAHAAN-PERUSAHAAN DI INDONESIA TAHUN 2017 - Abraham Wahyu Nugroho (Institute of Research and Community Outreach - Petra Christian University, 2020)
Communication is essential for the success of CSR program. However, research on CSR communication is still limited. Therefore, this paper aims to describe content of communication through CSR report in Indonesia. This research uses quantitative content analysis method with NVivo 10 text analysis support. The population of this research is 47 annual reports from public companies that received Investment Award in 2017. The results of this study indicate that every company had more than one social responsibility issue. Social responsibility was not only for communities but also for employee and customer. Rationale of CSR in Indonesia was not clear. Most of companies run CSR program through charity activities.